Prevalence of neonatal candidemia in a tertiary care institution in Hyderabad, South India - Rao, M. S. Srinivas; Surendernath, M.; Sandeepthi, M. (International Journal of Research in Medical Sciences, 2017)
Background: Candida species are known to be the most common fungal pathogens isolated from blood cultures of neonates. Recent reports from our country indicates trend towards an increasing prevalence of non-albicans candidemia. Candida species possess a number of virulence factors which enable them to cause hematogenously disseminated infections in susceptible hosts with increased morbidity and mortality. Objective of current study was to know the prevalence of nonalbicans candidemia in neonates and their antifungal susceptibility pattern. Methods:Blood samples from suspected cases of neonatal septicaemia were subjected to culture, incubated for 7 days and subcultures performed. Culture yielding pure growth of Candida were included for the study and identified by standard methodology. Antifungal susceptibility was performed. Results:A total of 255/500 (51%) cases were blood culture positive. Pure growth of Candida species was isolated from 52/255 (20.39%) cases. A total of 52 Candida isolates were obtained over a period of one year accounting for 20.39% of all neonatal septicemia cases. Among 52 isolates, 14/52 (26.92%) were Candida albicans, followed by C. tropicalis 19/52 (36.53%), C. glabrata 10/52 (19.23%), C. parapsilosis 4/52 (7.69%), C. guillermondii 2/52 (3.84%) and C. krusei 1/52 (1.92%). C. tropicalis, the most common species isolated, was 91 per cent susceptible to fluconazole, whereas C. parapsilosis and C. glabrata showed lower sensitivity rates of 67.8% and 62.5% respectively. Conclusion:In this study non albicans candida was the common isolate & they showed decreased resistance to Fluconazole. In neonatal septicemia speciation& antifungal susceptibility may help in management.